The Role of Wakaf In Establishing People's Welfare - Santoso, Dri; Musthofa, M Amin (Faculty of Sharia, IAIN Metro, 2022)
This research is related to the potential of waqf as a force for the development of people's welfare. Waqf is no longer synonymous with land earmarked for educational institutions, cemeteries, places of worship, or other things, but waqf can also be used as a source of strength to realize the welfare of the people and to move the empowering sectors of waqf assets which can be professionally managed by the nazir with good management. appropriate, then the benefits derived from the management of waqf will be wider in its designation so that in the future it can strengthen the role of waqf in improving the economy and welfare of the people.